EVALUASI PROGRAM PEMBELAJARAN TEACHING FACTORY DI SEKOLAH USAHA PERIKANAN MENENGAH - Fuadi, Afnan (Perspektif Ilmu Pendidikan, 2016)
The aim of this research is to evaluate the implementation of Teaching Factory Learning Program in SUPM Negeri Tegal. This research is a qualitative research using CIPP Model (Context, Input, Process, Product). The main subjects of this research were the teachesr of Teaching Factory and the students of class XII in Fish Processing Technology. The data were collected through participant observation using interview, observation, document study, and questionnaire. The research found that the implementation of the learning program Teaching Factory in SUPM Negeri Tegal are generally in good condition. This can be seen from the evaluation result that (1). Context Components show a good category; (2).Input Components show a good category; (3) Process Components show a very good category;.and (4) Product Components show a good category. The quality of the Teaching Factory learning program can be improved by treating the aspects of the low category in each stage of evaluation.